Endothelium-mediated vasodilation: associations with cardiometabolic diseases and their risk factors in aging - A. N. Ryabikov; M. S. Troshina; M. N. Ryabikov; Yu. Yu. Palekhina; E. O. Butakov; S. K. Malyutina (Российский кардиологический журнал, 2024)
Aim. To evaluate the association of flow-mediated vasodilation (FMD) with cardiometabolic diseases (CMDs) and their risk factors (RF) in old age.Material and methods. The study was conducted in the Russian population cohort of the HAPIEE project (Novosibirsk, 2015-2018). Endothelial function was assessed in a random subsample (788 men and women aged 55-84 years) using ultrasound measurements of the brachial artery FMD. Endothelial dysfunction (ED) was recorded with FMD <10%. Cardiovascular diseases (CVD) and risk factors were assessed using standard epidemiological methods.Results. The incidence of hypertension (HTN) was 78,8% (the same in men and women), major CVDs — 21,7% and 17,1%, type 2 diabetes (T2D) — 18,7% and 19,1% in men and women, respectively. The mean FMD values were 2,7% (SD 7,32) and 3,2% (7,19), while the prevalence of ED was 88,2% and 85,8% in men and women, respectively, and did not differ significantly by sex. Men with ED had higher levels of blood triglycerides (125,1 (71,23) vs 102,7 (45,79) mg/dl; p=0,033), waist/hip circumference indices (0,94 (0,050) vs 0,92 (0,076); p=0,009) and body weight (27,7 (45,79) vs 26,5 (4,36) kg/m2; p=0,077). In women, a tendency towards an association of ED with smoking was revealed (p=0,067). There were no associations of ED with HTN, T2D and CVD in men and women.Conclusion. The PMD test demonstrated a high incidence of ED in a population sample of 55-84 years old. ED is associated with metabolic risk factors in men and smoking in women. No associations of PMD with CMDs were found, presumably due to the high incidence of ED and cumulative disease in the elderly. Modification of metabolic risk factors and smoking cessation are relevant at any age to prevent the progression of ED.